Growth Performance of Broiler Chicken Fed with Different Levels of Fermented-Dried Azolla (Azolla pinnata) and IPIL-IPIL (Leucaena leucocephala) Leaf Meal - Silvestre, Shyn G.; Lava, Sheryl Mae N.; Perez, Zandro O. (International Journal of Poultry Science, 2026)
Objective: The study aimed to evaluate the effects of fermented-dried Azolla (Azolla pinnata) and Ipil-Ipil (Leucaena leucocephala) leaf meal supplementation on the growth performance and carcass quality of broiler chickens. The research sought to identify sustainable, locally available and cost-effective feed alternatives that could support the Philippine poultry industry’s shift toward environmentally friendly feeding practices. Materials and Methods: A total of 60-day-old broiler chicks were randomly assigned to four dietary treatments under a Completely Randomized Design for a period of 28 days. The treatments consisted of: (T1) pure commercial feed (control), (T2) 40 g Azolla + 40 g Ipil-Ipil/kg feed, (T3) 80 g Azolla/kg feed and (T4) 80 g Ipil-Ipil/kg feed. Parameters measured included feed consumption, feed conversion ratio (FCR), body weight gain, water intake, dressed weight, dressing percentage, carcass drip loss and net profit. Data were statistically analyzed to determine significant differences among treatment means. Results: Broilers supplemented with 80 g fermented-dried Azolla/kg feed exhibited the highest mean feed consumption (1.84 kg), the best FCR (1.73) and significantly greater weight gain (1.06 kg) compared to other treatment groups (p<0.05). No significant differences were observed in water intake, dressed weight, dressing percentage, or carcass drip loss among the treatments. Economic analysis indicated that birds receiving 80 g fermented-dried Azolla/kg feed achieved the highest net profit (Php 67.55 per head). Conclusion: The inclusion of fermented-dried Azolla at 80 g/kg feed improved growth performance and feed efficiency in broiler chickens without adversely affecting carcass quality. Given its local availability, high protein content and cost-effectiveness, fermented-dried Azolla presents a sustainable and eco-friendly alternative feed supplement for small-scale poultry producers in the Philippines. Further research is recommended to determine the long-term impacts and optimal inclusion levels for practical field applications.